Escaping the repugnant conclusion: Rank-discounted utilitarianism with variable population - Geir B. Asheim; Stéphane Zuber (University of Oslo, Department of Economics, 2012)
Evaluation of climate policies and other issues requires a variable population setting where population is endogenously determined. We propose and axiomatize the rank-discounted critical-level utilitarian social welfare order. It is shown to ll out the space between critical-level utilitarianism and (a version of) critical-level leximin. Moreover, it satis es many conditions and principles used to evaluate variable population criteria. In particular, it avoids the repugnant conclusion even when the critical level is zero.
Keywords: D63; D71; H43; Q56; 330; Social evaluation; population ethics; critical-level utilitarianism; social discounting; Soziale Wohlfahrtsfunktion; Utilitarismus; Bevölkerung; Soziale Diskontrate; Klimaschutz; Soziale Wohlfahrtsfunktion; Utilitarismus; Bevölkerung; Soziale Diskontrate; Klimaschutz